Party of the century : - Davis, Deborah (John Wiley, 2006)
Truman Capote's legendary masked ball, at New York City's Plaza Hotel on November 28, 1966, was a hyped-up media event meticulously masterminded by the self-promoting, social-climbing author of In Cold Blood. Davis (Strapless: John Singer Sargent and the Fall of Madame X) dishes up the menu, the decor, the outfits and the guest list of 540, clueing the reader in to how Capote dangled the prized invitations for months, snubbing early supporters like Carson McCullers as he determined who was "in" and who was "out." In choosing his guest of honor, Capote eschewed glamorous "swans" like Babe Paley and Marella Agnelli in favor of "dowdy" Washington Post publisher Katharine Graham. Actress Candice Bergen was bored at the ball; Capote's elevator man danced the night away with a woman who didn't know his pedigree; and Norman Mailer sounded off about Vietnam.